EFEK PENAMBAHAN FOOT CORE STABILITY EXERCISE PADA INTERVENSI CORE STABILITY EXERCISE DALAM PENINGKATAN POSTURAL CONTROL PASIEN PASCASTROKE - Sondang Samosir; Jerry Maratis; Kesit Ivanali (Jurnal Ilmiah Fisioterapi, 2024)
Objective: to analyze the improvement of postural control of post-stroke patients due to the addition of foot core stability to core stability exercise. Method: the implementation of this study is a type of "randomized controlled trial experimental" to analyze the inequality of the "addition of foot core stability intervention new bobath concept to a core stability exercise intervention in improving postural control of post- stroke patients". The sample consists of 20 patients and will be divided into two groups, namely treatment group I providing core stability exercise training, and treatment group II providing additional foot core stability exercise to core stability exercise intervention. Results: based on the results of the normality test by implementing the Shapiro-Wilk test method and from the results of Levene's test method homogeneity test obtained research data that is normally distributed and homogeneous. Then from the results of hypothesis testing with the Paired T-test method in treatment group I, the p-value is 0.36, which means "increased postural control is free from the influence of core stability exercise" while the test results in treatment group II obtained a p-value of 0.001, which means "increased postural control is influenced by the addition of foot core stability to core stability exercise". In addition, a p-value of 0.845 was also obtained from the results of the Independent T-test, which means "there was an inequality of functional pain reduction in treatment groups I and II". Conclusion: there is an increase in postural control which is influenced by the addition of foot core stability to core stability exercise.